2012
DOI: 10.1111/j.1743-6109.2012.02895.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovariectomy and Dehydroepiandrosterone (DHEA) on Vaginal Wall Thickness and Innervation

Abstract: Introduction One mechanism by which low sexual steroid activity observed after menopause could cause sexual dysfunction is by deficient vaginal innervation. Recently, it has been shown that intravaginal administration of dehydroepiandrosterone (DHEA) could produce beneficial effects on sexual dysfunction in postmenopausal women. Aim The goal of this study was to determine if DHEA could modify innervation in the rat vagina. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
(59 reference statements)
7
10
0
1
Order By: Relevance
“…This is in agreement with data from Pelletier et al [11] and Ahmed et al [18] but differs from the results of Ting et al [7] and Griebling et al [6]. However, Pelletier et al [11] just showed a significant decrease (59%) in vaginal PGP 9.5-ir fibers 9 months after OVX without further estrogen replacement therapy. Ahmed et al [18] focused on estrogen recovering function on pudendal nerve crush, omitting vaginal innervation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is in agreement with data from Pelletier et al [11] and Ahmed et al [18] but differs from the results of Ting et al [7] and Griebling et al [6]. However, Pelletier et al [11] just showed a significant decrease (59%) in vaginal PGP 9.5-ir fibers 9 months after OVX without further estrogen replacement therapy. Ahmed et al [18] focused on estrogen recovering function on pudendal nerve crush, omitting vaginal innervation.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, examination of plasma estrogen levels one month after OVX revealed that they were below the lower limit of the physiological range. Taken in combination with the results from Ting et al [7] and Pelletier et al [11], these data indicate that the dynamic changes in vaginal innervation after OVX may involve a short-term compensatory increase followed by a sustained decline. Furthermore, the discrepancy may partly be the narrow therapeutic range of estradiol, because the benefit of estrogen in vaginal innervation is diminished at larger doses.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Podobnych wyników nie uzyskano podczas doustnego podawania preparatów z DHEA [4]. Wytłu-maczeniem tego zjawiska może być silny wpływ DHEA na zwiększenie gęstości włókien nerwowych w ścianie pochwy, który wykazano w doświadczeniu na zwierzę-tach [12]. W innych badaniach Labrie i wsp.…”
Section: Dehydroepiandrosteron W Miejscowej Terapii Kobiet Z Objawamiunclassified